1981
DOI: 10.1111/j.1365-2141.1981.tb07241.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aplastic Presentation of Childhood Leukaemia: a Feature of Common‐ALL

Abstract: Transient pancytopenia preceded the onset of acute leukaemia in eight of 360 (2%) of children with acute lymphoblastic leukaemia (ALL) but did not occur in 70 cases of acute non-lymphoblastic leukaemia. The patients developed overt leukaemia within 5-38 weeks of first presentation with features of marrow failure. Immunological classification of blast cells was performed in six of the eight patients and all had phenotype of common-ALL (c-ALL). We conclude that the sydnrome of pre-leukaemia aplasia in childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 13 publications
1
39
0
1
Order By: Relevance
“…In addition to this extreme situation when very few CI)lObr'@" cells are sufficient to suggest the diagnosis ofALL, in a further 20-25% of cases median CD 10 AgE has significantly been above the normal range but with some overlap (30). This test is likely to be a valued diagnostic tool in "smoldering" leukemia (31,32 ). An important potential pitfall is, however, that in regenerating BM samples following chemotherapy some precursors and mostly SIg+, TdT-B lymphocytes may express CDlO with particularly high CDlO intensity ( 27.33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this extreme situation when very few CI)lObr'@" cells are sufficient to suggest the diagnosis ofALL, in a further 20-25% of cases median CD 10 AgE has significantly been above the normal range but with some overlap (30). This test is likely to be a valued diagnostic tool in "smoldering" leukemia (31,32 ). An important potential pitfall is, however, that in regenerating BM samples following chemotherapy some precursors and mostly SIg+, TdT-B lymphocytes may express CDlO with particularly high CDlO intensity ( 27.33).…”
Section: Discussionmentioning
confidence: 99%
“…Occasional cases of marrow hypoplasia or aplasia in childhood subsequently evolve into a frankly leukaemic phase, usually acute lymphoblastic leukaemia (ALL) (Melhorn et al, 1970;Breatnach et al, 1981;Saarinen & Wegelius, 1981;Klingemann et al, 1986;Cheng et al, 1987;Reid & Summerfield, 1992;D'Alessio et al, 1993;Liang et al, 1993;Matloub et al, 1993;Sato et al, 1993). In some cases the leukaemia becomes evident after a prolonged period of hypoplasia, but in others the patient appears to recover only to subsequently develop leukaemia.…”
mentioning
confidence: 99%
“…This suggests that the use of the combined assessment of these markers by QFC may distinguish more precisely between normal and leukemic B-precursors than the nonquantitative methods of flow cytometry, especially in the analysis of samples from children, who present a high percentage of normal B-precursors in BM that mimic the immunophenotypic features of ALL (11,32). Moreover, the approach described here may be useful in those cases of ALL presenting with pancytopenia, a condition of difficult diagnosis by morphological analysis alone (17,18).…”
Section: Discussionmentioning
confidence: 94%
“…The introduction of quantitative fluorescence cytometry (QFC) techniques allowed quantifying antigen expression in an accurate and reproducible manner (13,14) and previous reports have suggested that leukemic cells may express antigens at densities distinct from those presented by their normal counterparts (4,15,16). This method may be useful for MRD detection, as well as for the diagnosis of ALL, especially in those cases preceded by transient pancytopenia, a presentation more common in children and of difficult diagnosis (17,18).…”
Section: Introductionmentioning
confidence: 99%